Pengaruh Fasilitas Wisata dan Harga Terhadap Kepuasaan Pengunjung di Destinasi Wisata Tahura Kabupaten Bandung - Ghifar Firdaus; Irena Novarlia; Oman Sukirman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tourism is a sector that plays an important role in increasing Indonesia's foreign exchange. Therefore, it is mandatory for the tourist destination sector to pay attention so that every visitor who has visited a tourist destination feels satisfied after visiting the tourist destination. The aim of this research is to determine the influence of tourist facilities and prices on visitor satisfaction at the Tahura destination, Bandung Regency. The design of this research is quantitative with the population being visitors from the Tahura tourist destination and data collection was obtained through distributing questionnaires using Google Form and distributed to visitors who visited the Tahura tourist destination, Bandung Regency using a purposive sampling technique, with predetermined characteristics. The sample of this research consisted of 100 respondents. The data analysis technique from this research uses the classic assumption test which consists of the normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression. The data in this research was processed with the help of the IBM SPSS Statistics 25 for Windows application. The results of this research show that the variables of tourist facilities and prices have a significant effect on visitor satisfaction. In this research, the price variable has the greatest influence on the visitor satisfaction variable than other variables. It is hoped that this research will be useful for tourist destination managers so that they can maintain and improve tourist facilities. It is hoped that this research will be useful for the surrounding government so that they can pay attention to and improve the facilities and prices at the Tahura destination, Bandung Regency. It is hoped that this research will be useful for the Tourism Industry study program which will research Facilities. Tourism and Prices on Visitor Satisfaction, it is hoped that this research will be useful for researchers to develop tourist facilities in the Tahura destination, Bandung Regency.